Detailed online quizzes: facilitating holistic, integrated learning experience in operations management. (12th October 2009) - Kale, Rahul; Gupta, Saurabh; Fadil, Paul
Curriculum research in business schools points out that operations management (OM) is one of the more challenging courses to teach. Instructors have always struggled to enhance the student learning experience in OM courses. This article illustrates the development and utilisation of detailed online quizzes in a core OM undergraduate course and demonstrates its potential to achieve higher levels of student learning by mapping the quiz questions to the Bloom's taxonomy. The authors' argue that such quizzes lead to enhanced student performance and a more fulfilling course experience. To substantiate this position, the results of a quasi-experiment which test student perceptions of the overall learning experience found that these quizzes were both an effective and efficient way to overcome challenges inherent in OM courses. Multiple outcome measures were employed to validate these results. Practical implications of these results for OM professors and instructors are discussed.